2008
DOI: 10.1089/cpb.2007.0026
|View full text |Cite
|
Sign up to set email alerts
|

Do Aggressive People Play Violent Computer Games in a More Aggressive Way? Individual Difference and Idiosyncratic Game-Playing Experience

Abstract: This study investigates whether individual difference influences idiosyncratic experience of game playing. In particular, we examine the relationship between the game player's physical-aggressive personality and the aggressiveness of the player's game playing in violenceoriented video games. Screen video stream of 40 individual participants' game playing was captured and content analyzed. Participants' physical aggression was measured before the game play. The results suggest that people with more physical-agg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(24 citation statements)
references
References 23 publications
1
20
0
3
Order By: Relevance
“…For example, anger and psychoticism have been found to moderate the effect of VGV exposure on aggression, such that individuals who are high on these traits display greater aggression after VGV exposure than do individuals who are low on these traits (Giumetti & Markey, 2007;Markey & Scherer, 2009;Peng, Liu, & Mou, 2008). In the present study, low and high gamers reported similar levels of anger (Experiment 2); therefore, it seems unlikely that individual differences in this variable account for the relationship between gamer status and affective picture processing.…”
Section: Limitations and Conclusionmentioning
confidence: 49%
“…For example, anger and psychoticism have been found to moderate the effect of VGV exposure on aggression, such that individuals who are high on these traits display greater aggression after VGV exposure than do individuals who are low on these traits (Giumetti & Markey, 2007;Markey & Scherer, 2009;Peng, Liu, & Mou, 2008). In the present study, low and high gamers reported similar levels of anger (Experiment 2); therefore, it seems unlikely that individual differences in this variable account for the relationship between gamer status and affective picture processing.…”
Section: Limitations and Conclusionmentioning
confidence: 49%
“…Therefore, individuals who have difficulties identifying, expressing, and communicating emotions may overuse Internet gaming in order to regulate their emotions better and to fulfill their unmet social needs, and consequently alexithymia may result in high IGD severity (15). The results of a previous study suggest a correlation between physical-aggressive personality and aggressive style of playing (77). Yu (78) reported that the severity of IGD symptoms showed significant positive correlation with physical aggression.…”
Section: Discussionmentioning
confidence: 99%
“…Alongside popular opinion on the nature of violence in video games, there is sustained debate in psychology around causal links between games and subjective violence (see Dominick 1984 andSchutte et al 1988), which has spanned far into the 21 st century (see Anderson and Bushman 2001;Peng, Liu and Mou, 2008;Weber, Behr and Tamborini 2009;Shaw, Crosby & Porter 2014) following Dill & Dill's earlier suggestion of a 'need for more research ' (1998:407).…”
Section: Literature Reviewmentioning
confidence: 99%